Minnesota clergy’s attitudes on suicide prevention and likelihood to inquire about suicidal thoughts and intent - Hedman, Amy S. (Mental health, religion & culture, 2016)
Clergy are a recognised profession for suicide prevention and intervention in the United States. The current objective was to determine if clergy’s suicide prevention training, perceived roles in suicide prevention, and suicide prevention self-efficacy predicted likelihood to inquire about suicidal thoughts and intent. Among 367 Minnesota clergy surveyed, 30% reported a suicide in their congregation in the past year, and about one-third reported adequate training in suicide intervention strategies. The majority (85%) reported it was their role to provide education on suicide and mental health to their congregations, although 32% reported no or low ability to do so. Most (70%) stated, if concerned about a parishioner’s mental health, they would inquire about suicidal thoughts, but fewer (59%) stated they would inquire about suicidal intent. Significant, but weak, predictors of likelihood to inquire about suicide included self-efficacy and perceived role. Clergy could benefit from suicide prevention education, training, and support.